(untitled) (Conference Series, 2022)
It can be said that Jesus’s main mission on this earth was to preach about the Kingdom of God. The Gospel of Luke highlights the theme of the kingdom of God. Luke narrated the beginning of Jesus’ ministry when He read from the book of Isaiah in the synagogue in Nazareth. Jesus declared that Isaiah’s prophecy was being fulfilled in front of the audience in the synagogue. The prophecy talked of the Messiah’s ministry to four groups of people, and each of those groups was targeted by the Messiah’s ministry. They were clearly marginalized people then, and they can be related to the marginalized people in today’s society.